2018
DOI: 10.1194/jlr.m079806
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying catalytic activity of delta 6 desaturase from Glossomastix chrysoplasta and Thalassiosira pseudonana

Abstract: Delta 6 desaturase (FADS2) is a critical bifunctional enzyme required for PUFA biosynthesis. In some organisms, FADS2s have high substrate specificity, whereas in others, they have high catalytic activity. Previously, we analyzed the molecular mechanisms underlying high FADS2 substrate specificity; in this study, we assessed those underlying the high catalytic activity of FADS2s from and To understand the structural basis of this catalytic activity, GcFADS2 and TpFADS2 sequences were divided into nine sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…GcFADS12 possessed typical characteristics of other FADS12 family members, including three histidine‐rich conserved motifs (HXXHHK, HWXVXXTXLQH and HLVHH) and six transmembrane domains (Fig. ), and these observations were in agreement with our previous reports on Δ6 fatty acid desaturase . The amino acid sequence of GcFADS12 was highly similar to the one that S. Casaregola submitted to the GenBank (protein id: CDO51572.1), which was in agreement with the observation from our phylogenetic analysis of FADS12 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GcFADS12 possessed typical characteristics of other FADS12 family members, including three histidine‐rich conserved motifs (HXXHHK, HWXVXXTXLQH and HLVHH) and six transmembrane domains (Fig. ), and these observations were in agreement with our previous reports on Δ6 fatty acid desaturase . The amino acid sequence of GcFADS12 was highly similar to the one that S. Casaregola submitted to the GenBank (protein id: CDO51572.1), which was in agreement with the observation from our phylogenetic analysis of FADS12 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LB agar plates for plasmid construction in Escherichia coli Top 10 and SC‐U synthetic minimal medium for gene expression in S. cerevisiae were used as described previously . G. candidum was grown on Yeast Peptone Dextrose medium (containing 10 g·L −1 yeast extract, 10 g·L −1 peptone, 10 g·L −1 glucose and 20 g·L −1 agar) at 28 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the expression level of each chimeric desaturase in Pichia pastoris was determined by western blotting analysis as described previously ( Shi et al, 2015); each sample loading volume was adjusted to the same level according to the western blot results to determine desaturase activity of each chimera. Chimeric desaturase activity were analyzed by gas chromatography (GC) as described previously ( Shi et al, 2016; Shi et al, 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is important to study differences in the mechanisms underlying differential FADS12 activity in various species. At present, research on the catalytic mechanism of fatty acid desaturase is still in its infancy (Lee et al, 2016), except that the three-dimensional structure of FADS9 was analyzed and found to be mushroom-shaped (Bai, 2015; Wang, 2015) and the molecular mechanisms underlying FADS2 substrate specificity ( Shi et al, 2015) and catalytic activity ( Shi et al, 2018a) were analyzed in our previous study. However, studies on fatty acid desaturase in dominant strains of cheese have not yet been undertaken.…”
Section: Introductionmentioning
confidence: 99%